Notes on Plectranthus montanus (Lamiaceae)—a poorly known species in India and reduction of Coleus subbaraoi as one of its synonyms - Smitha, Kokkaraniyil; Sunojkumar, Purayidathkandy (Phytotaxa, 2017)
Taxonomic identity of Plectranthus montanus, a poorly known species from India is discussed by providing a detailed description, photographs and notes on its distribution. The specific status of Coleus subbaraoi is also discussed here. Critical study reveals that Coleus subbaraoi is conspecific with Plectranthus montanus and it is thus synonymized.